2008
DOI: 10.1111/j.1365-2648.2008.04851.x
|View full text |Cite
|
Sign up to set email alerts
|

Empowerment and its application in health promotion in acute care settings: nurses’ perceptions

Abstract: The theory of health promotion taught to participants does not seem to be applied in acute care settings. This raises the possibility that Registered Nurses acting as mentors and role models are convergent rather than divergent thinkers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 25 publications
0
14
0
1
Order By: Relevance
“…Other studies have found a directive approach by health professionals persists in locations where patient empowerment was part of the official policy 29 and where health professionals had been trained in empowering approaches. 30 Our study showed that participants chose to engage with the programme according to their needs (e.g. more information, motivation to persist with exercise, sustained changes in lifestyle).…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…Other studies have found a directive approach by health professionals persists in locations where patient empowerment was part of the official policy 29 and where health professionals had been trained in empowering approaches. 30 Our study showed that participants chose to engage with the programme according to their needs (e.g. more information, motivation to persist with exercise, sustained changes in lifestyle).…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…Chambers & Narayanasamy (2007) found that newly qualified staff nurses were capable of simultaneously holding two opposing value positions without any feeling of contradiction: a holistic view – the role based or public account, and a victim blaming view – personal agency or private account. In another study Chambers & Thompson (2009) found that despite the concept of patient empowerment being central to nursing theory, nurses continued to utilize a controlling power‐over approach to their health promotion practices. They propose that this is because biomedical values are more entrenched than nursing's concept of empowerment.…”
Section: Defining Valuesmentioning
confidence: 99%
“…They propose that this is because biomedical values are more entrenched than nursing's concept of empowerment. Thus both Chambers & Narayanasamy (2007) and Chambers & Thompson (2009) studies suggest that taught theory is not being practised because of the dominance of one set of values over another. It was this discord that led Argyris & Schön (1974) to classify action theories into 'espoused theories' and 'theories in use'.…”
Section: The Impact Of Personal Values On Nursing Practicesmentioning
confidence: 99%
“…Increasingly patients are being offered structured programs that encompass a great deal of education on lifestyle and medication management. Accordingly as a largely manageable and potentially preventable disease, there is an ever-increasing number of diabetic specialist education programs emerging internationally, at the same time patient education is increasingly incorporated into role of the nurse (Runciman et al 2006) and the nurse's role as health promoter is well recognised (Chambers & Thompson 2009).…”
Section: Introductionmentioning
confidence: 99%